Precedent phenomena and stereotypes in the linguo-cultural space: touch points and divergence points - А. А. Matveyeva (Вестник Самарского университета: История, педагогика, филология, 2020)
The article is devoted to the investigation of two types of cultural signs precedent phenomena and stereotypes. The deepened interest to the processes of intercultural communication, to the things predetermining its success or failure, to the things preconditioning certain evaluation of the communicative behaviour of a cultural community representative, not only defined the rapid development of the linguo-culturological paradigm but also required a re-interpretation of the interrelation between language, culture and mind questions. Precedent phenomena and stereotypes provide a fertile field for the investigation of such questions as the cultural markedness of language signs, cognitive structures verbalization, characteristics providing the commonness of a linguo-cultural space, the variety of aspects of a linguo-cultural personality. The aim of this article is to compare precedent phenomena and stereotypes in order to elicit their common features and differentiation lines. The investigation has been conducted on the English fiction and mass-media material which allowed to educe the ethnocultural connotations of precedent phenomena and stereotypes reflecting some stable representations of objects of reality in the mind of the language speakers. The investigation has revealed that the characteristics common for precedent phenomena and stereotypes include the sociocultural markedness of both cultural phenomena, their suprapersonal character, the reduced and invariant way of keeping in the mind of the linguocultural community representatives, the value-based and deictic character. As the investigation has shown, the differences between precedent phenomena and stereotypes take the lines emergence non-emergence, monoreferentiality polyreferentiality, metaphoricity non-metaphoricity, degree of behaviour modelling ability.